E-Bulling Scale And E-Victimization Scale: The Study of Validity and Reliability of Cigarette Addict Students at Ankara University - Çetin, Ebru; Cantürk, Nergis; Dağalp, Rukiye (The Bulletin of Legal Medicine, 2019)
Objective: The aim of this study is to make the validity and reliability studies of E-Bullying Scale and E-Victimization Scale developed by Lam and Li (2013), adapted into Turkish by Gençdoğan and Çıkrıkçı (2015) in Ankara University smoking addict students. Methods:The sample of this study consisted of 120 voluntary students from Ankara University who were smoking addict students of faculty of law, faculty of medicine and engineering faculty. The study data were collected with the Informed Voluntary Form and E-Bullying Scale consisting of six items, the E-Victimization scale consisting of five items.KMO and Bartlett’s test were used for content validity and Cronbach alpha coefficient was used for data reliability. Results:As a result of the validity analysis of the E-BullyingScale, the KMO value was 79,8%, the Barlett’s Test of Sphericity chi-squarevalue was found to be 323,480.The Cronbach alpha coefficient of the E-BullyingScalewas 0,834 andit was found to have a strong degree of reliability. As a result of the validity analysis of the E-VictimizationScale, the KMO value was 73,9% and the Barlett’s Test of Sphericity chi-squarevalue was found to be 224,418.The Cronbach alpha coefficient of the E-Victimization Scale was 0,808 and it was found to have a strong degree of reliability. Conclusion:The E-Bullying Scale and E-Victimization Scale adapted into Turkish by Gençdoğan and Çıkrıkçı have a high level of reliability and sufficient validity.The scale is recommended to be used for cases of the cyber bullying and cybervictimizationof smokingaddict university students.